2017
DOI: 10.1002/pbc.26783
|View full text |Cite
|
Sign up to set email alerts
|

Reduced‐toxicity alternate‐donor stem cell transplantation with posttransplant cyclophosphamide for primary immunodeficiency disorders

Abstract: We describe here the outcomes of reduced-toxicity alternate-donor stem cell transplant (SCT) with posttransplant cyclophosphamide (PTCy) for primary immunodeficiency disorders (PIDs) in eight children (haploidentical-seven and matched unrelated donor-one). The conditioning was with serotherapy (alemtuzumab-3/rabbit-anti-thymoglobulin-5); fludarabine, cyclophosphamide, and total body irradiation-5 (additional thiotepa-3); fludarabine and treosulfan-2; and fludarabine and busulfan-1. All received PTCy 50 mg/kg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 10 publications
0
22
0
1
Order By: Relevance
“…The ability of unconditioned DLI to improve mixed chimerism after BMT may ultimately be low, but data presented here and by others suggest that mixed chimerism may not require intervention with DLI, given that it can be stable over time and sufficient for phenotype reversal for some PIDs [23,24,27,32]. Although PTCy is known to decrease chronic GVHD incidence effectively, including in PID patients [23,25,[33][34][35], the complete absence of chronic GVHD in this study, confirmed on serial, comprehensive evaluations, is one of the most clinically important and promising findings. The low incidence of severe acute and chronic GVHD may be partly related to the gradual increase in donor T cells noted in most patients, allowing for early mixed chimerism, which may be tolerogenic.…”
Section: Discussionmentioning
confidence: 74%
“…The ability of unconditioned DLI to improve mixed chimerism after BMT may ultimately be low, but data presented here and by others suggest that mixed chimerism may not require intervention with DLI, given that it can be stable over time and sufficient for phenotype reversal for some PIDs [23,24,27,32]. Although PTCy is known to decrease chronic GVHD incidence effectively, including in PID patients [23,25,[33][34][35], the complete absence of chronic GVHD in this study, confirmed on serial, comprehensive evaluations, is one of the most clinically important and promising findings. The low incidence of severe acute and chronic GVHD may be partly related to the gradual increase in donor T cells noted in most patients, allowing for early mixed chimerism, which may be tolerogenic.…”
Section: Discussionmentioning
confidence: 74%
“…Multispeciality care, especially good pediatric intensive care support, is needed to improve outcomes as highlighted in the present paper [4]. Mixed chimerism was seen in 20% children in the present study; however, another study from India [10] has shown fully donor chimerism in a series of 8 patients undergoing reduced toxicity BMT with PTCy as GVHD prophylaxis. TCR alpha-beta/CD19 depletion is another new technique that can reduce GVHD rates tremendously with haploidentical donors.…”
mentioning
confidence: 54%
“…The main highlight of the paper by Uppuruli, et al [4] is the alternative donor transplant, which was performed in 47 out of 85 transplants (MUD-8, UCBT-14 and haploidentical-25). Newer reduced toxicity conditioning regimens using agents like Treosulfan and Fludarabine or Busulfan and Fludarabine with or without Thiotepa and Graft versus host disease (GVHD) regimens like PTCy or TCR alpha-beta/CD19 depletion from the donor graft have made BMT for PID safer [4,8,10]. Another heartening aspect is the spectrum of PID undergoing BMT in India -SCID, WAS and HLH were nearly 67% of total BMT in the present study but many other children with rare PID have also been transplanted [4].…”
mentioning
confidence: 99%
“…A higher risk of non-engraftment in cases of haploidentical donorship could be decreased due to myeloablative conditioning regimens. The recruitment of haploidentical donors for HSCT in children with primary immune deficiencies and sickle-cell anemia have been described in present studies [9,10,11]. PtCy prophylaxis was applied in all these cases showing its clinical efficiency.…”
Section: Discussionmentioning
confidence: 83%